Experimental study of near-field structure and thermo-hydraulics of supercritical CO2 releases. (15th August 2018) - Teng, Lin; Li, Yuxing; Hu, Qihui; Zhang, Datong; Ye, Xiao; Gu, Shuaiwei; Wang, Cailin
Abstract: CO2 transportation safety can directly affect the implementation of carbon capture, utilization and storage (CCUS) projects. The assessment of consequences of accidental release of supercritical CO2 are very important in the consideration of CO2 transportation safety. To ensure accurate prediction of the consequence of an accidental CO2 release, the near-field source terms including thermo-hydraulics have to be investigated, as the near-field jet flow structure significantly affects the evolution of solid CO2 particles. The aim of this work is to understand the under-expanded jet structure and thermo-hydraulics characteristics of supercritical CO2 releases from pressure vessels or pipelines. Experiments were developed to carry out controllable CO2 release from a high pressure vessel. The under-expanded jet structure of supercritical CO2 was recorded by a high speed camera. The jet velocity was measured using differential pressure sensors and a hot wire anemometer. In addition, the jet temperature, CO2 concentration, pressure and mass flow rate were also monitored. Through varying the release orifices in the experiment, the effects of size and pattern of the release orifices were analyzed. Graphical abstract: Image 1 Highlights: The jet structures in near-field from circular and rectangular orifices were recorded and compared. The evolutions of the Mach disk and the jet angle were analyzed quantitatively. The depressurization process was investigated based on the thermo-hydraulics in the vessel. The near-field temperature, jet velocity, mass flow rate and CO2 concentration are monitored. The effects of the orifice pattern on the discharge and dispersion are analyzed.